Hand properties of woven fabric treated with commercial softeners / Nor Kamalia Othman Adli... [et al.] - Othman Adli, Nor Kamalia; Mat Fuad, Nur Afiqah; Mohd Rahim, Nik Nur Raihani; Zainal, Halimatul Saadiyah; Nasir, Eryna; Jaafar, Zuraida; Abdul Ghani, Suzaini (Universiti Teknologi MARA, Negeri Sembilan, 2019)
This study was carried out to determine the hand properties of cotton woven fabric treated with three different brands of commercial softeners and to identify the stiffness relationship between objective and subjective assessment. The hand properties refer to the impression feels when the fabric is touched, squeezed, rubbed or otherwise handled. The cotton woven fabric was categorized into light to medium weight and medium to heavy weight type. Three different brands of softener; Brand A, Brand B and Brand C were used, and the fabric samples were washed by using top load home washing machine for 48 minutes in each cycle with the detergent and softener added into the washing machine dispenser drawer following the instruction label on the softener’s bottle. After washing process was done, the samples were evaluated objectively by their stiffness and panel experts did subjective assessment on the samples by investigating three attributes namely stiffness, softness, smoothness. The results obtained from objective and subjective evaluation were then analysed using Two-way ANOVA and Kruskal Wallis test respectively.